The Hardier You Are, the Healthier You Become. May Hardiness and Engagement Explain the Relationship Between Leadership and Employees’ Health? - Mazzetti, Greta; Vignoli, Michela; Petruzziello, Gerardo; Palareti, Laura (Frontiers in Psychology, 2019)
The main goal of this study was to delve deeper into the relationship that links transformational leadership to a greater general health status among employees. Based on the Job Demands-Resources model of occupational well-being, the current research investigated the role played by transformational leadership, as a job resource, in fostering individual hardiness, as a personal resource, that may in turn result in higher levels of work engagement and, consequently, a better general health status among employees. Data were collected on 358 white-collars employed in an Italian company. Most of them were women (52.9%) with a mean age of 44.42 years (SD = 9.22). To evaluate the hypothesis of a mediating role of employees’ hardiness and work engagement within the relationship between transformational leadership and workers’ general health, a bootstrapping approach was tested using a serial mediation model. In the current sample, enhanced levels of hardiness and work engagement among employees mediated the association between the perceived levels of transformational leadership and individual general health conditions. These findings corroborated the role of transformational leadership as a strategic job resource in enhancing employees’ hardiness and engagement with their work, which may in turn protect their general health status. Organizations willing to rely on a healthy workforce should implement HRM strategies focused on leadership training capable of boosting employees’ hardiness.